2021
DOI: 10.1111/ajgw.12522
|View full text |Cite
|
Sign up to set email alerts
|

Unripe grapes: an overview of the composition, traditional and innovative applications, and extraction methods of a promising waste of viticulture

Abstract: Unripe grapes (UGs) are a waste product of grapevine cultivation and an emerging source of several compounds, such as organic acids, phenolic compounds, vitamins and mineral salts, of great economic importance to the pharmaceutical, cosmetic and food industries. Traditionally, products made from UGs, such as verjuice and sour grape sauces, have been used as seasoning or acidifying agents. The health effects of grape compounds are described as anti-inflammatory, cardioprotective, anticancer and antidiabetic, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 133 publications
(250 reference statements)
0
16
0
Order By: Relevance
“…It is obtained by pressing unripe grapes using physical pressure (De Matos et al, 2017;Özturk and Şengun, 2019). Australia, New Zealand, South Africa, the United States, and Spain were among the first countries in the world to grow and use unripe grapes (Fia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obtained by pressing unripe grapes using physical pressure (De Matos et al, 2017;Özturk and Şengun, 2019). Australia, New Zealand, South Africa, the United States, and Spain were among the first countries in the world to grow and use unripe grapes (Fia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been used to prevent the enzymatic browning of fruits and vegetables (Tinello and Lante, 2017). It is also a common ingredient in Turkish sorbets (Ekici et al, 2018;Fia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rapid expansion of table grape planting area and the continuous improvement of viticulture management, fruit thinning has become a very extensive horticultural measure, so a large amount of solid waste such as thinned unripe grapes (TUR) is generated every year ( Guo et al, 2019 , Fia et al, 2021 , Wei et al, 2021 ). This new type of solid waste will be accumulated into the soil of the orchard and may become hosts for pathogens after decaying ( Dou et al, 2015 ), which accelerates the spread of crop diseases and increases the acidity of the soil, thereby disrupting the microbial community in the soil ( Mazzola, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TUR gradually attracts people's attention ( Bovo et al, 2016 , Fia et al, 2021 , Gutiérrez-Gamboa et al, 2020 , Piccardo et al, 2019 , Tinello and Lante, 2017 ) and becomes an urgent problem for the grape industry. Previous studies have revealed that grape juice made from TUR could be used as food-flavoring agent ( Dupas de Matos et al, 2018 ), such as replacing vinegar to make salad dressings and pickles.…”
Section: Introductionmentioning
confidence: 99%